Collateral and Monetary Policy - Singh, Manmohan (IMF Working Papers; Working Paper, 2013)
Financial lubrication in markets is indifferent to margin posting via money or collateral; the relative price(s) of money and collateral matter. Some central banks are now a major player in the collateral markets. Analogous to a coiled spring, the larger the quantitative easing (QE) efforts, the longer the central banks will impact the collateral market and associated repo rate. This may have monetary policy and financial stability implications since the repo rates map the financial landscape that straddles the bank/nonbank nexus.